PEMANFAATAN LOKALISASI PROSTITUSI UNTUK PENDAPATAN ASLI DAERAH (PAD) - Krista Surbakti; Permai Yudi (Universitas Quality, 2019)
This research aims to explain the benefits of prostitution localization if it is managed well by the regional government as part of the source of local revenue but in terms of the moral and ethical aspects of the community. The background of this research is because the government is unable to overcome prostitution problems in the region and this problem has long been unable to be resolved and becomes a controversial issue within the community, then the government can take positive and cooperative attitudes by utilizing it as a source of local revenue. This research was conducted in Bandar Baru Village. Deli Serdang Regency where prostitution often occurs in this environment but is not a localization of prostitution, in the sense that prostitution activities in the village are illegal and do not contribute significantly to the local treasury. The data collection technique used is Observation where observation is a way of seeing or observing an event from the outside to the inside and then describing it exactly as what is seen and observed. Observation is not limited to vision (visual), but the experience gained from hearing. The observation made was participation observation. Observation of participation with the technique